2022
DOI: 10.1093/trstmh/trac083
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Brucella in raw milk Minas artisanal cheese approved for consumption by official inspection agency in Brazil: assessment of prevalence and risk factors through One Health integrated approaches

Abstract: Background Minas artisanal cheese (MAC) from the Serro region is a Brazilian intangible cultural heritage. Produced from raw milk, it may carry zoonotic pathogens such as Brucella. This study included a randomized survey for the prevalence of Brucella-positive MAC and its associated factors. Methods MAC samples (n=55), each one from a different rural family-based cheese-processing agroindustry, were analysed for Brucella by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Frequently, Minas artisanal cheese microbiology is object from researchers, mainly with regard to the microbiological quality control of these products. In addition, microbiota studies have increased, aiming to identify the microorganisms present that may be responsible for the flavors attributed to these products (ANDREATTA et al, 2019;CAMARGO et al, 2021;DE SOUZA et al, 2021;SILVA et al, 2022).…”
Section: Follow-up Of News Published On Google Alerts About Artisanal...mentioning
confidence: 99%
“…Frequently, Minas artisanal cheese microbiology is object from researchers, mainly with regard to the microbiological quality control of these products. In addition, microbiota studies have increased, aiming to identify the microorganisms present that may be responsible for the flavors attributed to these products (ANDREATTA et al, 2019;CAMARGO et al, 2021;DE SOUZA et al, 2021;SILVA et al, 2022).…”
Section: Follow-up Of News Published On Google Alerts About Artisanal...mentioning
confidence: 99%
“…Likewise, Silva et al [ 54 ] found that 31% of Serro cheese samples were positive for the presence of field strains of Brucella sp., even though they came from serologically negative herds. Silva et al [ 55 ] found that, in 1.8% of the samples, B. abortus biovar 2 field strains were recovered by cultivation. These latter two studies highlight that their samples were taken from cheeses ripened for periods ranging from 4 to 8 days, and they were already marketed after an official certification that the herd is free of brucellosis.…”
Section: Introductionmentioning
confidence: 99%
“…In those cases, the cheese pH does not decrease as much as needed to inactivate Brucella . Therefore, the consumption of cheese with a low ripening time represents a great health hazard [ 54 , 55 ].…”
Section: Introductionmentioning
confidence: 99%